Vaccine hesitancy and coronavirus disease-19: Where do we stand? - Zaid Khan; Syed Quibtiya Khursheed; Shabir Ahmad Dar; Naveed Nazir Shah; Shuja Reagu; Majid Alabdulla; Inaamul Haq; Aaliya Mohi Ud Din Azad; Khurshid Ahmad Dar; Syed Suraiya Farooq; Zaid Ahmad Wani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Vaccine hesitancy is seen, globally, as a major factor that will determine future coronavirus disease-19 (COVID-19) spread and its effective management. This study aimed to identify COVID-19 vaccine perception, acceptance, confidence, hesitancy, and barriers among the general population. MATERIALS AND METHODS: This was an online survey which was developed and shared through social media platforms among the general population of Kashmir. The survey captured demographic data and used a validated hesitancy measurement tool. We analyzed the data using descriptive statistics and multivariable logistic regression using Stata 15 (Stata Corp. 2017. Stata Statistical Software: Release 15. College Station, TX, USA: Stata Corp LLC). RESULTS: A total of 835 responses were received. Most participants were males, with females compromising of 19.5% participants. 65.1% of participants were in the age group of 30-50, whereas 19.2% were below 30 years of age. 52.70% of respondents were willing to take the vaccine when available, while 32.5% of respondents were unsure about their decision of inoculation. The most cited reason for willingness to get vaccinated was an understanding of the disease and vaccination. 41.70% felt that the vaccines developed against COVID-19 have not been fully tested; therefore, concerns around the safety and its longer-term side effects were the reasons cited. Public health messaging should be tailored to address these concerns. CONCLUSIONS: Vaccine hesitancy is a global threat undermining the control of preventable infections. The government should take proactive steps to address the factors that may potentially impact the benefits expected from the introduction of a COVID-19 vaccine in the union territory.